War, immigration and COVID-19: The experience of Afghan immigrants to Iran Amid the pandemic - Mohammadsadeghi, Homa; Bazrafshan, Solmaz; Seify-Moghadam, Negar; Mazaheri Nejad Fard, Golnaz; Rasoulian, Maryam; Eftekhar Ardebili, Mehrdad (Frontiers in Psychiatry, 2022)
Introduction Afghanistan's domestic upheaval following the Taliban's invasion leads to massive displacement of its population. The number of Afghan refugees in Iran has dramatically increased since the Taliban's takeover of Afghanistan in August 2021. Multiple pre-and post-migratory traumatic experiences affect immigrants' physical, psychological, social, and economic wellbeing. The coronavirus outbreak, considered a traumatic experience in human life in the 21st century, added to their problems in Iran and exposed them to new challenges. This qualitative study aimed to investigate their experiences early before, during, and after immigration and the pandemic's challenges to their lives in Iran. Methods In the present qualitative study, ten Afghan residents living in Iran who immigrated to Iran legally or illegally since the summer of 2021 and the last year after the second Taliban invasion were selected via purposive sampling. A semi-structured interview was applied to gather the data, and the data were analyzed through Braun and Clarke's thematic analysis method. Results Ten male participants with a mean age of 26 y/o were interviewed. Their residence in Iran was between 20 days and 8 months. Four main themes were extracted. The first theme, the Tsunami of suffering, represents a disruption of the normal flow of life. Six subthemes, including loss, being near death, insecurity, sudden hopelessness, leaving the country involuntarily, and reluctance to explore underlying emotions, are included in this category. The second one, Lost in space, describes the participant's attempt to leave Afghanistan following the extensive losses and violent death threats. Their experiences are categorized into four subthemes: the miserable trip, encountering death, life-threatening experiences, and being physically and verbally abused. The third theme, with its five subthemes, try to demonstrate the participants' experiences after getting to their destination in Iran. The last one, Challenges of the COVID-19 explained the experience of Taliban return, war trauma, running away, and living as a refugee or immigrant coincided with the COVID pandemic. Discussion Our interviewees explained multiple and successive traumatic experiences of war, migration, and the pandemic. The central clinical features of survivors are fears of losing control, being overwhelmed, and inability to cope. They felt abandoned because not only lost their family support in their homeland but could not also receive support in Iran due to the pandemic-related social distancing and isolation. They were dissociated and emotionally numb when describing their experience, which is a hallmark of experiencing severe, unprocessed traumas. Conclusion Gaining a better understanding of Afghan refugees lived experiences may help provide them with better social and health care support. Proper mental and physical healthcare support and de-stigmatization programs may reduce the impact of multiple traumas on their wellbeing.